Improvement In Self-Reported Physical Functioning With Tiotropium/Olodaterol In Central And Eastern European COPD Patients - Valipour, Arschang; Tamm, Michael; Kociánová, Jana; Bayer, Valentina; Sanzharovskaya, Maria; Medvedchikov, Alexey; Haaksma-Herczegh, Monika; Mucsi, János; Fridlender, Zvi; Toma, Claudia; Belevskiy, Andrey; Matula, Bohumil; et al. (International journal of chronic obstructive pulmonary disease, 2019)
BACKGROUND: Reduced physical activity is associated with increased morbidity and mortality in patients with COPD. Studies suggest that treatment with the long-acting muscarinic antagonist tiotropium and the long-acting β2-agonist olodaterol increases exercise capacity. This study assessed the effects of a fixed-dose combination (FDC) of tiotropium/olodaterol (delivered via Respimat®) on physical functioning in patients with stable COPD in a "real-world setting". METHODS: An international, open-label, single-arm, non-interventional study conducted in nine countries measuring changes in self-reported physical functioning in COPD patients treated with tiotropium/olodaterol 5/5 μg FDC for approximately 6 weeks. The primary endpoint was therapeutic success, defined as a minimum 10-point increase in the 10-question Physical Functioning Questionnaire (PF-10) score. Secondary endpoints included absolute change in PF-10 from Visit 1 to Visit 2, patient general condition (measured by Physician's Global Evaluation score) and patient satisfaction with the treatment and device (assessed by Patient Satisfaction Questionnaire at the end of the study period). RESULTS: Therapeutic success was observed in 67.8% of 7218 patients (95% CI 66.7, 68.8) in the final analysis set after approximately 6 weeks of treatment with tiotropium/olodaterol. Mean change in PF-10 score between Visit 1 and Visit 2 was 16.6 points (95% CI 16.2, 17.0). Therapeutic success was 64.3% (95% CI 63.0-65.6%) in patients with infrequent (≤1) and 76.1% (95% CI 74.3-77.9%) in patients with frequent (≥2) exacerbations (p<0.0001). Patient general condition improved as indicated by an improvement in Physician's Global Evaluation scores between visits. Most patients were very satisfied or satisfied with tiotropium/olodaterol treatment in general (81%), reported inhalation satisfaction (85%), and satisfactory handling of the device (84%). 1.3% of patients reported an investigator-defined drug-related adverse event. CONCLUSION: Treatment with tiotropium/olodaterol led to an improvement in self-reported physical functioning in patients with COPD.
Keywords: Humans; lidé středního věku; zpráva o sobě; fixní kombinace léků; Self Report; COPD; chronic obstructive pulmonary disease; Female; Aged; physical functioning; tiotropium; senioři; lidé; Europe; non-interventional study; Benzoxazines; tiotropium bromid; ženské pohlaví; Male; Middle Aged; Tiotropium Bromide; benzoxaziny; chronická obstrukční plicní nemoc; Pulmonary Disease, Chronic Obstructive; Exercise; Drug Combinations; mužské pohlaví; cvičení; Evropa; olodaterol